Implementation of Good Village Governance in Village Development - Achmad Aminudin (Social and Political Science Faculty - Universitas Tidar, 2019)
AbstractVillage development studies always a hot issue to be studied. Especially in current political year (2019). The national village development policies have made significant changes, but there are still some obstacles and challenges in their implementation, starting from the actors of policy until the achievements of the programs implementated in the village. This study aims to understand how the principles of Village Governance can be implemented in the implementation of the Village Fund Allocation Program. By using technical descriptive-qualitative analysis, this study can explain the implementation of the principles of good village governance that have been ongoing. The data analysis used in this study is domain analysis. According to Bungin (2007) domain analysis techniques are used to analyze the description of research objects in general or at the surface level, but relatively intact about the object of the research. After observing, interviewing, and reviewing the literature on the implementation of Village Funds, it can be concluded that all the provisions and policies in implementing the Village Law, especially village finance, can be implemented well for all levels of government. However, in actual shows that there are several indicators of good village governance that have not been implemented properly. The findings include: 1.Village financial governance is still relatively not good; 2.Partisipatory, integrated and harmonized village planning with regional and national planning has not been effective; 3.Abuse of power and authority which results in legal problems tend not to decrease; 4.Quality of service to the community still has not increased.Keywords: Good Village Governance; Implementation; Village Development.